PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN SUMBER BELAJAR DI LINGKUNGAN PENDIDIKAN ANAK USIA DINI - Devi Yasmin; Sudarti Sudarti (Jurnal Buletin Al-Ribaath, 2017)
Education for kids is very important, especially from an early age. The right of every kid to gain proper education in order to develop knowledge and improving human resources. One model of applied learning is learning in environmental resource management. Parit Baru village Sungai Raya subdistrict of Kubu Raya has PAUD Permata Hati that have land that is not being used as a source of learning, the environmental conditions that can be used as a source of learning in early childhood learning is not being used to to source of learning  but it used to place waste throwers and grown shrubs, then the team IbM trying to help improve the knowledge and skills to empower communities to manage learning resources in early childhood environment Permata Hati to be environmentally beneficial for early childhood as a learning. The programs succesfully changed surrounding environment being more productive as kid’s learning sources. Kids can use their surrounding environment to learn espiacially about entrepreneurship It is expected that the managers, teachers, and the community can maintain and care for the existing environment to be a source of learning in PAUD Permata Hati. Keywords : learning source, environment, PAUD